Allergic Reactions to Serine Protease-Like Proteins of Staphylococcus aureus - Nordengrün, Maria; Abdurrahman, Goran; Treffon, Janina; Wächter, Hannah; Kahl, Barbara C.; Bröker, Barbara M. (Frontiers in Immunology, 2021)
In cystic fibrosis (CF) infectious and allergic airway inflammation cause pulmonary exacerbations that destroy the lungs. Staphylococcus aureus is a common long term colonizer and cause of recurrent airway infections in CF. The pathogen is also associated with respiratory allergy; especially the staphylococcal serine protease like proteins (Spls) can induce type 2 immune responses in humans and mice. We measured the serum IgE levels specific to 7 proteases of S. aureus, 5 Spls and the staphopains A and B, in 76 CF patients and 46 adult controls (ELISA). Then we compared cytokine release and phenotype of T cells that had been stimulated with Spls between 5 CF patients and 5 controls. CF patients had strongly increased serum IgE binding to all Spls but not to the staphopains. Compared to healthy controls, their Spl stimulated T cells released more type 2 cytokines (IL-4, IL-5, IL-13) and more IL-6 with no difference in the secretion of type 1 or type 3 cytokines (IFNγ, IL-17A, IL-17F). IL-10 production was low in CF T cells. The phenotype of the Spl-exposed T cells shifted towards a Th2 or Th17 profile in CF but to a Th1 profile in controls. Sensitization to S. aureus Spls is common in CF. This discovery could explain episodes of allergic inflammation of hitherto unknown causation in CF and to extend the diagnostic and therapeutic portfolio.